A step forward in enhancing the health-promoting properties of whole tomato as a functional food to lower the impact of non-communicable diseases - Natali, Pier Giorgio; Piantelli, Mauro; Sottini, Alessandra; Eufemi, Margherita; Banfi, Cristina; Imberti, Luisa (Frontiers in Nutrition, 2025)
Nutritional interventions facilitating the consumption of natural, affordable, and environment-compatible health-promoting functional foods are a promising strategy for controlling non-communicable diseases. Given that the complex of tomato micronutrients produces healthier outcomes than lycopene, its major antioxidant component, new strategies to improve the health-supporting properties of the berry are ongoing. In this context, a whole tomato food supplement (WTFS), enriched by 2% olive wastewater containing a complex of healthy nutrients with converging biologic activities, has recently been developed, which is superior to those present in tomato commodities or obtained with whole tomato conventional processing methods. WTFS equals the antioxidant activity of N-acetyl-cysteine and interferes with multiple inflammation and cellular transformation-sustaining metabolic pathways. In interventional studies, WTFS inhibits prostate experimental tumors and improves benign prostate hypertrophy-associated symptoms with no associated side-effects. Although WTFS may be susceptible to further improvements and clinical scrutiny, its composition embodies the features of advanced functional foods to ease adherence to dietary patterns, that is, the Mediterranean diet, aimed at contrasting and mitigating the low-grade inflammation, thus being interceptive or preventive of non-communicable diseases.